Mix design and properties of reactive powder concrete with diatomaceous earth as cement replacement. Issue 1 (September 2020) - Saidi, T; Hasan, M; Riski, A D D; Ayunizar, R R; Mubarak, A
Abstract: Reactive powder concrete (RPC) consuming a large amount of Portland cement results in high cost. To reduce the cement used in RPC, the silica fume and ground granulated blast-furnace slag have been used as cement replacement. However, those materials are not available in Aceh Province - Indonesia. The objective of this research is to propose the mix design of RPC composed of locally available materials. In this paper, the mix design of RPC using calcined diatomaceous earth powder as partial cement replacement is presented. The iron ore powder was used as filler, and river sand with a diameter of less than 1 mm was used as aggregate. To maintain the workability of concrete, superplasticizer was added. The bulk density, specific gravity as well as particle size distribution of Portland cement, diatomaceous earth powder, iron ore powder and river size were tested. The modified Andreasen and Andersen model was utilized. The mix proportion of materials was determined using an optimization algorithm based on the least-squares method. Furthermore, all materials were mixed to produce RPC; and then the properties of fresh and hardened concrete i.e. workability, air content, compressive strength, splitting tensile strength, and flexural strength, were tested. The relative slump flow decreases with the increase of diatomaceous earth binder. The RPC with diatomaceous earth powder has a lower 7 days compressive strength but high flexural strength and splitting tensile strength.